Challenges faced and coping strategies adopted by injecting drug users during COVID-19 Lockdown-A qualitative study - Shruti Vashisht; Shreya Jha; Shashi Kant; Nishakar Thakur; Sanjay Rai (Wolters Kluwer Medknow Publications, 2023)
Background: The lockdown due to COVID-19 pandemic has adversely affected the lives of vulnerable population, including the injecting drug users (IDUs). The objective of the study was to document the coping mechanism adopted by IDUs and suggest measures to mitigate the adverse effects, if similar situation were to arise in future. Materials and Methods: A qualitative study was conducted at the Targeted Intervention Non-Government Organizations catering to IDUs in Delhi and Ghaziabad district of Uttar Pradesh. Four focus group discussions among 41 IDUs and 7 key informant interviews of the NGO staff were conducted in the study. The Hindi recordings were coded and the data analysis was performed manually using grounded theory approach. Results: We found that the lockdown affected the lives of most of the IDUs and they found it difficult to access the harm reduction services. To cope with this, many IDUs started following alternate methods to support the drug habits. There was an increase in reuse of needles and syringes. Conclusion: The lockdown during COVID-19 and the resulting challenges negatively impacted the physical and mental health of the IDUs. We recommend that in any similar future scenario, travel pass may be issued to the IDUs and the TI-NGO personnel.